Proposal of Load Aware Routing for OSPF Routing Protocol - Macha, Tomas; Krkos, Radko; Novotny, Vit (Communications - Scientific letters of the University of Zilina, 2013)
This paper deals with route cost assignment using one of the most commonly used routing protocols - Open Shortest Path First (OSPF). The limitation of this protocol is that the algorithm does not take actual link load into consideration. This paper proposes using an alternate costing strategy to avoid this problem. The alternate strategy uses an integer value representing the load of a link as the additive component of metric. Since the link load is a dynamic variable, Exponential Weighted Moving Average is used to counter quick changes. This paper proposes a novel approach to calculate OSPF metrics, aimed to better distribute the load in network.